Chronic Fatigue and Postexertional Malaise in People Living With Long COVID: An Observational Study. Issue 4 (13th January 2022) - Twomey, Rosie; DeMars, Jessica; Franklin, Kelli; Culos-Reed, S Nicole; Weatherald, Jason; Wrightson, James G
Abstract: Objective: People living with long COVID describe a high symptom burden, and a more detailed assessment is needed to inform rehabilitation recommendations. The objectives were to use validated questionnaires to measure the severity of fatigue and compare this with normative data and thresholds for clinical relevance in other diseases; measure and describe the impact of postexertional malaise (PEM); and assess symptoms of dysfunctional breathing, self-reported physical activity, and health-related quality of life. Methods: This was an observational study with a cross-sectional survey design (data collection from February 2021 to April 2021). Eligible participants were adults experiencing persistent symptoms due to COVID-19 that did not predate the confirmed or suspected infection. Questionnaires included the Functional Assessment of Chronic Illness Therapy–Fatigue Scale and the DePaul Symptom Questionnaire–Post-Exertional Malaise. Results: After data cleaning, 213 participants were included in the analysis. The total Functional Assessment of Chronic Illness Therapy–Fatigue Scale score was 18 (SD = 10) (where the score can range from 0 to 52, and a lower score indicates more severe fatigue), and 71.4% were experiencing chronic fatigue. Postexertional symptom exacerbation affected most participants, and 58.7% met the PEM scoring thresholds used in people living with myalgic encephalomyelitis/chronic fatigue syndrome. Conclusion: Long COVID is characterized by chronic fatigue that is clinically relevant and at least as severe as fatigue in several other clinical conditions. PEM is a significant challenge for this patient group. Because of the potential for setbacks and deteriorated function following overexertion, fatigue and postexertional symptom exacerbation must be monitored and reported in clinical practice and in studies involving interventions for people with long COVID. Impact: Physical therapists working with people with long COVID should measure and validate the patient's experience. Postexertional symptom exacerbation must be considered, and rehabilitation needs to be carefully designed based on individual presentation. Beneficial interventions might first ensure symptom stabilization via pacing, a self-management strategy for the activity that helps minimize postexertional malaise.